Digitalization of Museum Communications in Libraries - Kovalchuk Tatyana А. (Bobcatsss, 2023)
Libraries of the Republic of Belarus, following the world trends, have been actively collecting and preserving museum collections in their funds for more than a decade. The most effective forms of popularizing museum collections of libraries and presenting information about them have always been traditional museum expositions and exhibitions. However, the aggravation of the epidemiological situation around the world in 2020 associated with the spread of сoronavirus infection (COVID-19) significantly accelerated the transition of museum collections to the online space, which allowed library users around the world to familiarize themselves with the collections without leaving their homes. To this end, libraries are digitizing their collections and using digital communication tools to promote them on the Internet. In order to the online promotion of designated collections be effective, library professionals must have the knowledge, skills and abilities necessary to implement technology and establish communication between users and museum collections of libraries through library sites and social media. The ways of presenting materials about museum objects and collections through library sites can be virtual tours, audio and video guides, virtual exhibitions and catalogs. An effective presentation tool, with the help of which a visual and fascinating demonstration of any museum expositions actually organized in the space of libraries is possible, is a virtual tour. The organization of virtual excursions on library websites requires library specialists know the technologies of their creation using special software. To use audio and video guides (tours), which are a reference guide in the form of audio or video recording, library specialists need to know the technologies for creating videos. Technologies briefly describes the objects that are exhibited in museum expositions of libraries. Also specialists need to know the technologies for digitizing items in museum collections of libraries and creating audio recordings with a narrated story about them. The technology of creation of virtual exhibitions involves demonstration on websites of libraries of specially selected and digitized museum items, which are organized and structured according to thematic areas, artistically designed, and creates a single museum image. The most difficult thing is to create virtual catalogs. They are a database with a list of digitized items from museum collections of libraries and descriptions to them. Virtual catalogs also have filters for searching by name, type, etc. To use virtual catalogs as a tool to popularize museum collections, librarians need to know the technologies for their development and creation, as well as the technology for digitizing items in museum collections of libraries and replenishing the database with them. To organize communication with target audiences on social networks, library specialists need to be able to determine the goals and objectives of popularizing museum collections of libraries, target audience and social networks, develop a content strategy, organize and evaluate the effectiveness of the work done. The possibilities of social networks make it possible to maintain interactive headings, organize polls, contests, quizzes, etc., which is an effective means of popularizing museum collections of libraries among its users.